Effect of Different Cultural Practices and Fertilization on the Regeneration of Degraded Lasiurus sindicus Grassland in Extreme Arid Conditions of Jaisalmer, India - Kumawat, R N; Santra, P; Sinha, N K (Annals of Arid Zone, 2018)
A field trial was conducted in factorial randomized block design with three cultural practices of till, no-till and burning in the main plot and two levels of fertilization viz. control and 40 kg N + 20 kg P ha-1 in subplots on the degraded Lasiurus sindicus (Sewan) grassland to ascertain the regeneration behavior of the grass at Jaisalmer, Rajasthan during the summer 2010. The results of the study revealed that cultural practice of no-till recorded 94.46 and 100.47 higher green and dry fodder yield than the tilling practice. The root volume, dry weight of rhizome and roots were also 38.63, 92.89 and 49.57% higher with no-till practice than the tilling practice. Application of fertilizer increased the fresh and dry fodder yield, dry crown weight, dry root weight and fresh root volume per tussock by 85.93, 125.63, 75.51, 67.36 and 63.02% more than the control, respectively. The practice of no-till recorded maximum numbers of tillers/tussock, tiller height, nodes/tillers, leaves/tussock and spikes/tussock compared to till and burning practices. The tussock diameter of Sewan grass was double in size at all the stages under no-till compared to till treatment. The effect of fertilization was more on tillers/tussock that was 93.16, 83.91, 77.37 and 78.49% higher than the control at 15, 30, 45 and 60 days after treatment of cultural practices and fertilization, respectively application. The protection of the degraded grassland and supply of nutrients sufficed for the revival of Sewan grassland in the Jaisalmer conditions.Key words: Burning, fertilizer, regeneration, Sewan, till.